Prevalence of teenage pregnancy and its obstetric and perinatal outcomes in a rural tertiary care hospital - Krishna Madala, Venkata Ramya; Gangadharan, Keshav; Shivaraju, Pradeep; Mateti, Devivaraprasad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Teenage pregnancy has been reported as one of the leading causes of death in adolescent girls in both developed and developing countries. In developed countries teenage pregnancies are most common in unmarried girls whereas in developing countries like India where early marriages are more common, teenage pregnancies are seen mostly in married women. Methods: In this retrospective observational study, data between January 2018 and December 2019 was studied; data was evaluated using MS excel for statistical purpose. In the present study, only pregnant women less than 20 years were included. Results: Out of 6,028 pregnant women delivered during this period, 686 i.e. 11.3% age of women were less than 20 years, 609 (88.7%) had delivery at term and the remaining 77 (11.2%) women had preterm delivery. As per this study, incidence of hypertensive disorders were 12.24%, 5.5% were associated with anemia and most of them had vaginal delivery (65.01%) including induced and instrumental; cesarean section was 35.5%. In present study, 24.1% babies were of low birth weight and 3.49% of babies were intrauterine growth restricted (IUGR) babies. Conclusions: This study showed hypertensive disorders were the most common maternal complication and the incidence of vaginal delivery was higher compared to that of cesarean section, incidence of anaemia was less compared with other studies. Proper antenatal care, institutional delivery and postnatal care can reduce fetal and maternal complications in childbearing women in teenage age group.